Voltammetric characterization of [ReO]3+ containing complexes - Cerda, María Fernanda (2007)
In the present work, the voltammetric profiles of Au-pc in 1 mM solutions of K[ReVOCl2(L)] (L = dianions of H2hida or H2eida; hida, n-(2,6-dimethylphenyl carbamoylmethyl)imino diacetic acid, and eida, 2,6-diethyl ida) complexes were evaluated. The obtained electrochemical response was the result of the contributions coming from the [ReO]3+ core (Epa at ca. 0.2 V vs. Ag/AgNO3) and the carboxylic group of the ligand. There where also observed redox contributions ascribed to the presence of perrhenate coming from the decomposition of the complex with the lost of ligands, in agreement with the low stability of the studied complexes. copyright The Electrochemical Society.